2016
DOI: 10.3389/fmicb.2016.02032
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Cattle and Bison Inoculum on Ruminal Fermentation and Select Bacterial Communities in an Artificial Rumen (Rusitec) Fed a Barley Straw Based Diet

Abstract: This study evaluated the effect of increasing the proportion of bison relative to cattle inoculum on fermentation and microbial populations within an artificial rumen (Rusitec). The experiment was a completely randomized design with a factorial treatment structure (proportion cattle:bison inoculum; 0:100, 33:67, 67:33, and 100:0) replicated in two Rusitec apparatuses (n = 8 fermenters). The experiment was 15 d with 8 d of adaptation and 7 d of sampling. Fermenters were fed a diet of 70:30 barley straw:concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
(48 reference statements)
3
11
0
Order By: Relevance
“…The effluent, FPA, and FPB microbial N (MN) production was calculated as described by Ribeiro et al (2015) and Oss et al (2016). True DM and N disappearance was calculated by subtracting the microbial mass from feed residues.…”
Section: Rusitec Evaluation Of Recombinant Fibrolytic Enzymes For Barmentioning
confidence: 99%
“…The effluent, FPA, and FPB microbial N (MN) production was calculated as described by Ribeiro et al (2015) and Oss et al (2016). True DM and N disappearance was calculated by subtracting the microbial mass from feed residues.…”
Section: Rusitec Evaluation Of Recombinant Fibrolytic Enzymes For Barmentioning
confidence: 99%
“…Furthermore, rumen microbiome is the key player in the variations in feed efficiency of ruminants [28]. Therefore, comparative studies that aim to understand the differences in rumen microbiome between ruminant species could lead to explain the fiber digestion and methane emission in efficient animals and identifying key microbes in rumen fermentation, which offer the possibility to regulate the rumen microbiota in less efficient animals towards more efficient microbial pathways and targeting of specific microorganisms to improve animal performance [8,21,29].…”
Section: Introductionmentioning
confidence: 99%
“…Rumen fermentation models offer the opportunity to study the rumen microbiota in the absence of host factors. Oss et al (2016) showed that when RUSITEC fermenters were inoculated with rumen fluid from bison (Bison bison) and cattle (Bos taurus) in combination, dry matter disappearance improved compared to each fluid alone. By broadening the range of microbes in the inoculum, in the absence of host factors, it may have been possible for a community structure to emerge that was better adapted to the in vitro conditions than those that could emerge from the bison or cattle fluids alone.…”
Section: Introductionmentioning
confidence: 99%